FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 DI RSUD K.R.M.T WONGSONEGORO SEMARANG - Berkat Br Nababan; Lintang Dian Saraswati; Muflihatul Muniroh (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Indonesia with a growth of 152% or from 8.426.000 people in 2000 to 21.257.000 people in 2030. The proportion of cases of Type 2 DM in Semarang City Hospital in 2014 amounted to 1.83 percent and in 2015 3.22 percent of all Hospital in Semarang City . The purpose of this study to determine the factors associated with blood sugar levels in patients with Diabetes Mellitus type 2 in RSUD KRMT Wongsonegoro Semarang. The method of this research is analytic observational with cross sectional approach. This research is done by observation and interview method. The sampling technique used in this research is random sampling technique. The result of bivariate analysis showed that there was no significant correlation between food intake (p = 0,765), drug intake (p = 0,731), physical activity (p = 1,000), stress level (p = 0,094 ), family support (p = 0,453), and smoking status (p = 0,459) with blood glucose level in Type 2 DM patient. So, it can be concluded that nothing related to blood sugar level.